Ninth International Symposium on Symbolic and Numeric Algorithms for Scientific Computing (SYNASC 2007) 2007
DOI: 10.1109/synasc.2007.17
|View full text |Cite
|
Sign up to set email alerts
|

'Descente Infinie' Induction-Based Saturation Procedures

Abstract: In [11], we have shown that implicit induction and saturation proof techniques share the same logic, witnessed by an inference system implementing the Fermat's 'Descente Infinie' induction principle. As a case study, a simple paramodulation-based inference system has been proved as an instance of it. In this paper, we detail the instantiation method to treat general saturation-based systems and apply it to analyse a non-trivial resolution-based system. We also propose a methodology to build variants of existin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In this case, the Noetherian induction principle becomes a contrapositive version of the 'Descente Infinie' induction principle we have previously used in [20,21,22,23]:…”
Section: Noetherian Induction For Implicit Induction Proofsmentioning
confidence: 99%
“…In this case, the Noetherian induction principle becomes a contrapositive version of the 'Descente Infinie' induction principle we have previously used in [20,21,22,23]:…”
Section: Noetherian Induction For Implicit Induction Proofsmentioning
confidence: 99%
“…If the set of new conjectures is not empty, the current conjecture is saved as premise. φ[r i ] p indicates that φ has the subterm r i at position p. In [48,49], it has been shown that ∪ n i {φ i } from similar superposition-based inference rules is a strict cover set of φ, as it is the case for ConjSup.…”
Section: Formula-based Induction Principlesmentioning
confidence: 99%
“…It is conducted by a methodology to build sound implicit induction procedures using the compositional properties of contextual cover sets. The methodology also allowed to represent saturation-based inference systems as instances of the general inference system [48,49]. It witnesses that the implicit induction and saturation-based procedures share the same logic.…”
Section: Formula-based Induction Principlesmentioning
confidence: 99%